Test of Mechanical Roaster Rotary Type with Soybean Commodity - Syahnan Riady Nasution; Saipul Bahri Daulay; Lukman Adlin Harahap (Jurnal Rekayasa Pangan dan Pertanian, 2013)
Mechanical roaster has multi functional for bean commodities. The aim of study was to test mechanical coffee roaster rotary type with soybean commodity. This research was conducted at the Laboratory of Agricultural Engineering, Faculty of Agriculture, University of North Sumatra in November until December 2012 by study of literature, experiment, observation, and testing of the equipment. Parameters observed were effective capacity, moisture content, and the economic analysis. The results showed that the effective capacity of a mechanical soybean roaster  type rotary  was 5.590 kg/h, the highest water content was 7.07% and the lowest was 5.70%, while from the economic analysis, the BEP was 3.885,42 kg, NPV 16% and 20% were Rp. 13. 758.853,97 and    Rp. 12.086.672,76, respectively and the IRR was 52,91%. Keywords: mechanical roasters, soybean, water content, effective capacity.